2006
DOI: 10.1515/cclm.2006.065
|View full text |Cite
|
Sign up to set email alerts
|

Release of anandamide from blood cells

Abstract: Background: Endogenous ligands of cannabinoid receptors (endocannabinoids), in particular anandamide (arachidonylethanolamide), have been recognized as being of crucial importance in a variety of physiological functions. Plasma concentrations of anandamide have been measured in a number of investigations; however, discrepant data on ''normal'' anandamide plasma concentrations were reported. Since this might be caused by pre-analytical variables, we investigated the impact of different sample handling condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 29 publications
(41 reference statements)
2
56
1
Order By: Relevance
“…The levels of AEA measured by both LPE and SPE methods in plasma from non-pregnant woman was 0.64 nM and 1.38 nM (range 0.51-3.99 nM) for term pregnant women. These data differ from those reported by other groups, 2.58 and 3.73 nM for non-pregnant women [23,24]. The difference could be related to the physiological state or the timing of processing of their biological samples.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The levels of AEA measured by both LPE and SPE methods in plasma from non-pregnant woman was 0.64 nM and 1.38 nM (range 0.51-3.99 nM) for term pregnant women. These data differ from those reported by other groups, 2.58 and 3.73 nM for non-pregnant women [23,24]. The difference could be related to the physiological state or the timing of processing of their biological samples.…”
Section: Discussioncontrasting
confidence: 96%
“…Furthermore, it has also been demonstrated that use of silica SPE, but not C18 SPE, can lead to loss of deuterium from internal standard [21] causing inaccuracy in the determination of AEA. In addition, these methods were developed for brain tissue using concentrations of AEA ranging from 20-2000 pmol/g [10,11,21] which are not representative of the low pmol/ml AEA concentrations observed in plasma [12,13,16,17,24]. An additional problem when modifying AEA extraction methods for tissues for use with bio-fluids is that extraction media are added to tissues in large quantities (40-500 fold w/v) [10,11,21] which is possible because of the small size of the tissue samples being extracted.…”
Section: Discussionmentioning
confidence: 99%
“…Several aspects, e.g., clinical condition, concomitant medication, fasting/nonfasting state, and possibly also sex differences, need to be considered. Furthermore, some methodological precautions must be followed to avoid artificially increased anandamide levels in blood (34).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of endocannabinoids by high performance liquid chromatography tandem mass spectrometry (HPLC-MS/MS) in three recent studies in rat brain and human plasma have reduced analysis times to between 7-15 min. However, these studies have either a: not been validated [18], b: are used for brain tissues not plasma [19] or c: had comparatively poor limits of detection [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although plasma AEA concentrations have been determined in a number of human cohorts, the mean AEA concentrations reported have varied considerably between studies, from 0.37 nM [18] and 2.58 nM [21] to 3.73 nM [20]. This 10-fold variability between studies suggests that plasma AEA concentrations can be difficult to determine routinely and thus a robust, validated analysis method is needed.…”
Section: Introductionmentioning
confidence: 99%